Life cycle and development rate of Hemipyrellia ligurriens (Wiedemann) (Diptera: Calliphoridae) during monsoon season in South India: applications in estimation of postmortem interval - M. P. Reject Paul (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 2021)
Hemipyrellia ligurriens, considered as one of the forensically important blow fly species, has a wide distribution in many countries including India. To conduct forensic entomological investigations involving deaths of livestock, human beings and wild animals, standard life cycle data should be prepared for the local blow fly species under various weather conditions. Reliable forensic entomological data specific to geographic locations in India are not available presently to assist the post mortem interval assessment. In this study, life cycle and the rate of development of H.ligurriens was determined during monsoon season in Kerala, South India. Survival rate observed from egg to adult emergence was 44.68 %. Total duration of development of the species from oviposition till adult emergence was 462.57 h. Growth curves based on the age, specific length parameter and time taken for development of each larval stage was constructed. This development model would be helpful for the medical, veterinary and law enforcement officials in forensic estimation of post mortem interval by analyzing the length parameters of larvae collected from decomposed dead bodies of humans, cadavers of wild animals and livestock.